PERANCANGAN VIDEO ANIMASI PEMBELAJARAN LITERASI DI SD NEGERI 101944 DELI MUDA - Saragih, Yudha Darma; Harianja, Eva Julia G.; Lumbantoruan, Gortap (Universitas Methodist Indonesia, 2023)
Animated Literacy Learning is an animation that provides learning about literacy, specifically focusing on reading materials in the form of original data messages to its users. The reading literacy material includes learning letter recognition, reading skills, and reading exercises. This research aims to develop an application that can be used to enhance students' skills, particularly in reading. Additionally, the learning process with this application is expected to be more enjoyable and can further motivate users to learn, as it incorporates images, sounds, and animations. The objective of this learning application is to train and enhance students' literacy skills, as it also includes exercises to assess the students' proficiency level in the given teaching materials. The research methodology employed in this study includes literature review, data collection, needs analysis, system design, implementation, and evaluation. The final outcome of this research is an animated literacy learning video specifically designed for students at SD Negeri 101944 Deli Muda. It is anticipated that this video will increase students' interest and literacy skills while providing an enjoyable and interactive learning experience.